Development of natural fibre for environmental and sustainable advancement - Atiqah A.; Ansari M.N.M.; Zahidi M.M.M.; Begum S.; Yahya Z.; Alkhadher S.A.A. (Inderscience Publishers, 2023)
Composite materials; Cost engineering; Hardness; Hemp; Impact strength; Kenaf fibers; Polyurethanes; Sustainable development; Thermosets; Chemical treatments; Energy sector; Environmental pollutions; High performance products; Reinforced polymer composites; Renewable resource; Sustainable environment; Value-added engineering; Tensile strength; chemical analysis; composite; environmental management; hardness; natural resource; polymer; renewable resource; sustainable development; Hibiscus cannabinus